Distribuição espaço-temporal da classe Copepoda na Baía de Guanabara, RJ, Brasil - Machado, Carla Ferreira (2002)
This study presents the space-time of the Class Copepoda for Guanabara Bay from March 1998 to November 1999. Bimonthly, surface horizontal net hauls were carried out at 8 sites, using a conic-cylindrical net of 200μm mesh size. Vertical tows at Guanabara Bay entrance site were done to complement the species list. Twenty-five species of copepods were identified, and the most abundant and frequent ones were Acartia tonsa, Acartia lilljebörgi and Paracalanus parvus. It was possible to observe an increasing north-to-south gradient in organisms abundance and in species diversity, which was probably associated to salinity variations and circulation pattern. Moreover, the cluster analysis showed a tendency for abundance and species diversity to increase during wintertime.